2001
DOI: 10.1080/10584580108011961
|View full text |Cite
|
Sign up to set email alerts
|

The influence of synthesis temperature on structure properties of SrTiO3 ferroelectric films

Abstract: To cite this article: V. E. Loginov , A. V. Tumarkin , M. V. Sysa , O. U. Buslov , M. M. Gaidukov , A. I. Ivanov & A. B. Kozyrev (2001) The influence of synthesis temperature on structure properties of SrTiO 3 ferroelectric films,The results of structure investigations of SrTi03 films depending on synthesis temperature are presented and electrical characteristics of 4-electrode planar capacitors based on prepared films are investigated. Finally, the technological conditions of high structure quality SrTi03 fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Oxygen vacancy formation energies were calculated using the following equation:Effalse(VOfalse)=EnormalvacEnormalpris+normalμnormalOwhere Evac and Epris denote the total energy of the GB structures with and without oxygen vacancies, respectively. By using the typical experimental growth condition of SrTiO 3 , i.e., temperature of 750°C and an oxygen partial pressure of 10 −9 atm, we obtained the ΔnormalμnormalO=2.04 eV. The calculated formation energies of oxygen vacancy before and after structural relaxation are plotted in Figure A and B, respectively, with respect to the vacancy positions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxygen vacancy formation energies were calculated using the following equation:Effalse(VOfalse)=EnormalvacEnormalpris+normalμnormalOwhere Evac and Epris denote the total energy of the GB structures with and without oxygen vacancies, respectively. By using the typical experimental growth condition of SrTiO 3 , i.e., temperature of 750°C and an oxygen partial pressure of 10 −9 atm, we obtained the ΔnormalμnormalO=2.04 eV. The calculated formation energies of oxygen vacancy before and after structural relaxation are plotted in Figure A and B, respectively, with respect to the vacancy positions.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we generate GB phase diagrams for oxygen vacancy with respect to synthesis temperature ( T ) and oxygen partial pressure (pnormalO2). SrTiO 3 can be synthesized under a wide variety of experimental conditions, with most syntheses at temperatures between 600 and 1400°C, and oxygen partial pressures between 10 −12 and 10 −0.7 atm . Therefore the GB phase diagrams are made to correspond to these T and pnormalO2 ranges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations have revealed that STO film samples, whose structural characteristics are close to those of the single crystals, also exhibit the best electri cal properties, in particular, the low level of microwave loss [8]. Consequently, the studies aimed at producing STO single crystal films are justified from the view point of their microwave properties.…”
Section: Introductionmentioning
confidence: 98%
“…The relatively low level of dielectric loss (tanδ) over a wide frequency range makes the STO films very prom ising as a material for the use in microelectronic microwave devices. The possibilities of using the STO films for microwave applications at room temperature were demonstrated in [7,8]. The main disadvantage of the STO films in comparison with the BSTO films is the necessity of using high control voltages to achieve an acceptable controllability (for STO based capaci tors, it is usually C(0 V)/C(300 V) ≈ 2 [9]).…”
Section: Introductionmentioning
confidence: 99%